Behavior of recycled brick block concrete-filled FRP tubes under axial compression. (1st November 2019) - Jiang, T.; Wang, X.M.; Chen, G.M.; Zhang, J.J.; Zhang, W.P.
Highlights: Waste brick is reused as recycled brick blocks (RBBs) at least 60 mm in size. RBBs are mixed with fresh concrete (FC) to form a compound concrete (RBBC). RBBC features a strength between those of RBBs and FC and increased discreteness. RBBC-filled FRP tubes (RBBCFFTs) are proposed to improve performance of RBBC. RBBCFFTs show significantly enhanced strength and deformability compared to RBBC. Abstract: Waste brick accounts for a significant fraction of China's construction and demolition (C&D) waste. A new reprocessing approach in which the waste brick is crushed into blocks (recycled brick blocks, RBBs) distinctly larger in size than normal-sized aggregate and mixed with fresh concrete to form a new type of compound concrete (recycled brick block concrete, RBBC) is proposed in this paper. To improve the compressive behavior of RBBC, an outer fiber reinforced polymer (FRP) tube is used in this study as both the confining and protective device for RBBC; it simultaneously serves as a stay-in-place formwork (i.e., RBBC-filled FRP tubes, RBBCFFTs). Compression tests were conducted on RBBC and RBBCFFTs with the mix ratio and size ratio of RBBs and thickness of FRP tube as variables. The test results show that RBBC has a compressive strength between those of the RBBs and the fresh concrete, and it can derive significantly enhanced strength and deformability under FRP confinement. However, the tested RBBCFFTs exhibited increased discreteness in compressive behavior owing to the large difference in strength between the RBBs and the fresh concrete, and the inhomogeneous spatial distribution of RBBs. In addition, the first portion of RBBC's stress–strain curve appears elongated under FRP confinement. This phenomenon is believed to be due to the delay in formation of the major cracks in RBBC when it is confined in an FRP tube, allowing the integrity of RBBC to be sustained until a higher axial stress level than when the FRP tube is absent. Finally, a design-oriented stress–strain model for RBBCFFTs is developed within the framework of Lam and Teng's design-oriented stress–strain model for FRP-confined normal concrete. The proposed model is shown to have reasonably good accuracy.